Some issues related to the exercise of the pre-emptive right to purchase agricultural real estate by the National Support Centre for Agriculture - Litwiniuk, Przemysław (Przegląd Prawa Rolnego, 2021)
The practice of reserving the right of pre-emption for the State Treasury, local government units and other entities by way of a statute should be regarded as an emanation of the State. The frequency with which this practice is exercised is Poland has been increasing at a very high rate in recent years. The statutory right of pre-emption concerning agricultural real estate, reserved for the State Treasury in the provisions of the Act of 11 April 2003 on shaping the agricultural system is of particular legal and practical significance. The subject of this article is the legal characteristics of this entitlement granted to the National Support Centre for Agriculture, and examination whether exercising this right in the State Treasury's name is arbitrary (discretionary) or whether it ought to be exercised with a view of fulfilling constitutional and statutory prerequisites of State’s interference in the ownership right. The author presents an opinion that the current statutory form and the practice of the execution of the pre-emptive right to purchase agricultural real estate by the National Support Centre for Agriculture raise serious doubts of constitutional nature. These doubts result from the lack of a clear statutory separation of the prerequisites for the application of this right granted to the State Treasury in relation to private agricultural real estate. He also proposes to determine a statutory catalogue of such premises and to establish a reliable administrative procedure where necessary, regarding State’s interference in private-legal relationships, so that decisions made by public administration are not arbitrary.